Enterprise Resource Planning (ERP) Business Process Reengineering with Accelerated SAP (ASAP) and Kanban Methods (Case Study: Sahana Bali Craft) - Liukae, Herry Daniel Prasetia; Pratama, I Putu Agus Eka; Putri, Gusti Agung Ayu (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 12 No 1 (2024): Vol. 12, No. 1, April 2024DO - 10.24843/JIM.2024.v12.i01.p04, 2024)
Sahana Bali Craft, a handicraft company that produces Ayaman Bags typical of Tengenan Village, Karangasem Regency, Bali where through the results of interviews and observations, it was revealed that this company faced obstacles in recording production and cost calculations that were still done manually, application of the Make to Order concept was not well integrated, and the company did not have an Enterprise Resource Planning system and re-engineering was carried out. This research recommends the implementation of business process re-engineering as an effort to improve business process efficiency with the ASAP and Kanban methods. The ASAP method is used in designing ERP systems to optimize costs, time, and available resources, while the Kanban method is applied in project management at the business blueprint and realization stages. The business process engineering has been tested with the User Acceptance Testing method and shows 1320 < 1718 < 1760 which means that the proposed business process system is considered positive or quite successful for the company.